The impact and perceptions of standing desk interventions on movement patterns and physical, mental, and academic outcomes in university students: a scoping review - María Eugenia Visier-Alfonso; Mairena Sánchez-López; Bruno Bizzozero-Peroni; Valentina Díaz-Goñi; Shkelzen Cekrezi; Iván Suazo; Vicente Martínez-Vizcaíno (BMC Public Health)
Abstract Background The use of standing desks may reduce sedentary behavior and, in turn, improve other health and academic outcomes. However, the evidence is sparse among university settings. The aim of this scoping review was to identify and map evidence for the effects of standing desk interventions on sedentary behavior and physical, mental, and academic outcomes in university students, as well as instructors and students’ perceptions of this type of equipment in the classroom. Methods A scoping review was conducted in accordance with the Joanna Briggs Institute and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Review guidelines. PubMed, Web of Science, Scopus, PsycINFO, PubPsych and ERIC databases were searched for qualitative and quantitative studies from their inception to 2024. Narrative synthesis and network plots were used to summarize the available evidence. Results Seventeen studies involving 2886 university students and 163 instructors were included. Fourteen studies were experimental and three were cross-sectional. In seven studies standing desks improved movement patterns (sitting and standing time in the classroom) and in four studies improved mental health outcomes (anxiety, mood, stress, and positive or negative feelings). Four studies analyzed pain and discomfort, one found significant improvements and three found mixed results. Eleven studies analyzed academic and classroom outcomes and seven found significant improvements in the standing desks group and five did not. Additionally, the use of standing desks was accepted and positively perceived by students in ten studies and by instructors in two. Conclusions The implementation of standing desks at university settings could be a behavioral intervention for improving movement patterns and mental health. However, the extant evidence is sparse; further long-term, high-quality trials are needed to draw robust conclusions.